Electroencephalographic Features of Presumed Hepatic Encephalopathy in a Pediatric Dog with a Portosystemic Shunt—A Case Report - Raluca Adriana Ștefănescu; Vasile Boghian; Gheorghe Solcan; Mario Darius Codreanu; Mihai Musteata (Life)
Hepatic encephalopathy (HE) in dogs is a metabolic disorder of the central nervous system that occurs secondarily to liver dysfunctions, whether due to acquired or congenital causes. A portosystemic shunt is the presence of abnormal communications between the hepatic vessels (portal and suprahepatic veins). As a result of this, the blood brought from the digestive tract through the portal vein bypasses the liver, and the unmetabolized components of the portal bloodstream enter directly into systemic circulation, causing clinical symptoms of metabolic encephalopathy (HE). A 3-month-old Bichon canine patient with a history of seizures secondarily to a portosystemic shunt (PS), confirmed through color Doppler ultrasound exam and computed tomography, was presented for evaluation. The typical electroencephalographic (EEG) traces recorded were characterized by the presence of bilateral symmetrical triphasic waves, resembling non-convulsive status epilepticus. The presence of this EEG pattern is useful in choosing the best therapeutic option in order to not accentuate the HE sings and, consequently, to decrease the mortality risk due to a prolonged status epilepticus.